2016
DOI: 10.1038/ncomms11801
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding short circuits from zinc metal dendrites in anode by backside-plating configuration

Abstract: Portable power sources and grid-scale storage both require batteries combining high energy density and low cost. Zinc metal battery systems are attractive due to the low cost of zinc and its high charge-storage capacity. However, under repeated plating and stripping, zinc metal anodes undergo a well-known problem, zinc dendrite formation, causing internal shorting. Here we show a backside-plating configuration that enables long-term cycling of zinc metal batteries without shorting. We demonstrate 800 stable cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
173
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(187 citation statements)
references
References 22 publications
(29 reference statements)
0
173
0
1
Order By: Relevance
“…22,23 The problem with overstating the impact of results derived from flooded beaker cells without proper context is that such experiments are essentially electrodeposition studies. For example, the ''dendrite problem'' of zinc-based batteries can be approached from many angles including additives to the electrolyte, 24 charging sequence optimization, 25 anode architecture design, [8][9][10] or the literal angle can be 180 , that is ''backside-plating'' as demonstrated by Higashi et al 26 These authors showed, using a flooded cell, that insulating the cathode-facing side of the cell would slow the formation of dendrites because the growing needles would have a more tortuous path when initiating shorts.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…22,23 The problem with overstating the impact of results derived from flooded beaker cells without proper context is that such experiments are essentially electrodeposition studies. For example, the ''dendrite problem'' of zinc-based batteries can be approached from many angles including additives to the electrolyte, 24 charging sequence optimization, 25 anode architecture design, [8][9][10] or the literal angle can be 180 , that is ''backside-plating'' as demonstrated by Higashi et al 26 These authors showed, using a flooded cell, that insulating the cathode-facing side of the cell would slow the formation of dendrites because the growing needles would have a more tortuous path when initiating shorts.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…The major problemsn eed to be solved are metal corrosion,d endrite formation, and hydrogen evolution. rechargeable zinc-ionb attery containing mild acidic electrolyte, Ni-Zn battery) [18][19][20] whereas in hybrid batteries (e.g. rechargeable zinc-ionb attery containing mild acidic electrolyte, Ni-Zn battery) [18][19][20] whereas in hybrid batteries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods are available for ZAFCs to improve their performances. However, we often neglect the fact that apart from cell materials or dendrite growth, the management of air flow and electrolyte can provide a more effective and simpler way of improving the cell performance. In this study, the electrolyte management of ZAFCs was explored in depth using a circulating electrolyte and the following conclusions were drawn.…”
Section: Discussionmentioning
confidence: 99%